Prognosis-related factors in intensive care unit (ICU) patients with hematological malignancies: A retrospective cohort analysis in a Chinese population. - Liu, Jing; Cheng, Qian; Yang, Qing; Li, Xin; Shen, Xiaohui; Zhang, Lina; Liu, Zuoliang; Khoshnood, Kaveh (Hematology (Amsterdam, Netherlands), 2015)
Objectives This study investigates the link between patient characteristics and mortality in patients with hematological malignancies (HM) in three university-affiliated hospitals in Hunan, China. Methods We conducted a detailed retrospective chart review of 121 sequential intensive care unit (ICU) admissions with HM over a 5-year period. Outcome measures were short- and long-term mortality rates and were correlated with physiologic and therapeutic factors. We also evaluate the performance of two severity-of-illness scoring systems in this population, particularly the value and trend of the sequential organ failure assessment (SOFA). Results The rates for ICU, 1-month and 6-month mortalities were 60.3, 85.9, and 90.9%, respectively. Invasive mechanical ventilation (IMV) was associated with worse outcomes at all time points. Both acute physiology and chronic health evaluation and SOFA scores had positive correlation with ICU mortality. An increase or no change in SOFA over the course of the admission or during the first 48 hours after admission was the most powerful adverse predictor. IMV use and renal dysfunction had a negative effect on the 1-month survival. Conclusion Patients with HM have less access to intensive care resources in Hunan, China. The use of IMV, APACHII at admission, and SOFA trend have a strong predictive value in this population. Based on our results, we propose a panel of parameters for use when considering ICU transfer to guide patient management.